Nematic Fluctuations in the Non-Superconducting Iron Pnictide BaFe1.9−xNi0.1CrxAs2 - Gong, Dongliang; Yi, Ming; Wang, Meng; Xie, Tao; Zhang, Wenliang; Danilkin, Sergey; Deng, Guochu; Liu, Xinzhi; Park, Jitae T.; Ikeuchi, Kazuhiko; Kamazawa, Kazuya; Mo, Sung-Kwan; et al. (Frontiers in Physics, 2022)
The main driven force of the electronic nematic phase in iron-based superconductors is still under debate. Here, we report a comprehensive study on the nematic fluctuations in a non-superconducting iron pnictide system BaFe_1.9-xNi_0.1Cr_xAs_2 by electronic transport, angle-resolved photoemission spectroscopy (ARPES) and inelastic neutron scattering (INS) measurements. Previous neutron diffraction and transport measurements suggested that the collinear antiferromagnetism persists to x=0.8, with similar Néel temperature T_N and structural transition temperature T_s around 32 K, but the charge carriers change from electron type to hole type around x= 0.5. In this study, we have found that the in-plane resistivity anisotropy also highly depends on the Cr dopings and the type of charge carriers. While ARPES measurements suggest possibly weak orbital anisotropy onset near T_s for both x=0.05 and x=0.5 compounds, INS experiments reveal clearly different onset temperatures of low-energy spin excitation anisotropy, which is likely related to the energy scale of spin nematicity. These results suggest that the interplay between the local spins on Fe atoms and the itinerant electrons on Fermi surfaces is crucial to the nematic fluctuations of iron pnictides, where the orbital degree of freedom may behave differently from the spin degree of freedom, and the transport properties are intimately related to the spin dynamics.